Influence of different lubricants on the retentive force of LOCATOR® attachments – an in vitro pilot study. Issue 7 (9th September 2015) - Srinivasan, Murali; Schimmel, Martin; Kobayashi, Mariko; Badoud, Isabelle; Ammann, Patrick; Herrmann, François R.; Müller, Frauke
Abstract: Objective: The aim of this in vitro pilot study was to evaluate the influence of an artificial saliva (AS) lubricant on the retentive force of a stud‐type attachment (LOCATOR ® ) for implant overdentures (IODs). Methods: Twenty custom‐made models simulating a two‐IOD with parallel implant situation were fabricated using LOCATOR ® attachments. The in vitro testing was carried out with an Instron ® universal testing machine for a total of 10, 000 insertion–removal cycles, for each model, in two different aqueous test mediums (Group 1: 0.9% sodium chloride solution (NaCl), n = 10; Group 2: AS, n = 10). Changes in the mean retentive force ( F ) were plotted against the cycle numbers #10, #100, #1000, #5000, and #10, 000. Mixed regression models were applied for statistical analyses. Results: A mixed regression (not considering interactions) predicted, compared to cycle #10, higher retentive forces at cycles #100 ( P < 0.0001), #1000 ( P = 0.017), similar forces at #5000 ( P = 0.277), and lower forces at #10, 000 ( P = 0.012); there was no overall effect of the medium ( P = 0.159). A second statistical model, employing the interaction term "cycle##medium", confirmed similarly the effect. Although the interaction term was significant at cycle #100 ( p = 0.045), there was no significant difference between the two groups ( P = 0.140). Conclusion: In this in vitro pilot experiment, there was no difference in mean retentive forces of the LOCATOR ® attachments when tested with either 0.9% NaCl or a Glandosane ® ‐like artificial saliva lubricant. A larger scale study may still confirm the superiority of either lubricant for quasiclinical bench experiments.